2017
DOI: 10.1128/aem.00444-17
|View full text |Cite
|
Sign up to set email alerts
|

Genome Stability in Engineered Strains of the Extremely Thermophilic Lignocellulose-Degrading Bacterium Caldicellulosiruptor bescii

Abstract: Caldicellulosiruptor bescii is the most thermophilic cellulose degrader known and is of great interest because of its ability to degrade nonpretreated plant biomass. For biotechnological applications, an efficient genetic system is required to engineer it to convert plant biomass into desired products. To date, two different genetically tractable lineages of C. bescii strains have been generated. The first (JWCB005) is based on a random deletion within the pyrimidine biosynthesis genes pyrFA, and the second (M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
21
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 49 publications
(59 reference statements)
0
21
0
Order By: Relevance
“…Thus far, Caldicellulosiruptor bescii is the only species in the genus that has been shown to have a tractable genetic system, and it has been successfully used to study and improve the features of this bacterium (8,(11)(12)(13)(14)(15). Recently, a kanamycin antibiotic selection marker was developed that significantly improves the ability for genetic manipulation of C. bescii (16) and facilitated development of genetically stable strains for metabolic engineering (17).…”
Section: Importancementioning
confidence: 99%
“…Thus far, Caldicellulosiruptor bescii is the only species in the genus that has been shown to have a tractable genetic system, and it has been successfully used to study and improve the features of this bacterium (8,(11)(12)(13)(14)(15). Recently, a kanamycin antibiotic selection marker was developed that significantly improves the ability for genetic manipulation of C. bescii (16) and facilitated development of genetically stable strains for metabolic engineering (17).…”
Section: Importancementioning
confidence: 99%
“…In fact, the large repetitive sequences within this locus led to errors in genome assembly of the GDL in the initial C. bescii genome sequence (10). This was recently corrected and resulted in the relocation of the Athe_1859 to -1857 genes between Athe_1867 and Athe_1866 (11). Transcriptomic and proteomic analyses of highly cellulolytic Caldicellulosiruptor species showed that the GDL is highly transcribed and expressed during growth on both crystalline cellulose and switchgrass (3,12).…”
Section: Importancementioning
confidence: 99%
“…The most studied from this genus is Caldicellulosiruptor bescii that cometabolizes five‐carbon (C5) and six‐carbon (C6) sugars (Blumer‐Schuette et al, ), thereby rapidly and extensively converting lignocellulose‐derived complex carbohydrates, such as arabinan (C5), mannan (C6), galactan (C6), xylan (C5), and cellulose (C6), into fermentation products (Zurawski et al, , ). C. bescii has already been engineered to produce ethanol from switchgrass (Chung, Cha, Guss, & Westpheling, ), and further improvements in the genetics toolbox for this bacterium (Lipscomb, Conway, Blumer‐Schuette, Kelly, & Adams, ; Williams‐Rhaesa et al, ) bode well for developing strains with enhanced carbohydrate degradation capacity (Conway et al, ) and increased levels of metabolically engineered products (Williams‐Rhaesa et al, ). The complex structure and content of plant biomass exacerbates the microbial degradation of the carbohydrate content present as cellulose and hemicellulose, even at low biomass loadings.…”
Section: Introductionmentioning
confidence: 99%